Effects of an Analogue of Negative Reinforcement on the Selection of Culturants - Ribeiro, Damom Cruz (2021)
The present research investigated the effect of a negative reinforcement analog on the selection of culturants and, unlike previous studies, sought to eliminate the interference of the negative punishment of other culturants. Three laboratory microcultures, with three participants in each of them, were exposed to an ABAB design. The participants chose between colored lines, numbered from 1 to 10. In the Positive Reinforcement condition (A), target culturants produced cultural consequences. In the Negative Reinforcement condition (B), cultural consequences were subtracted every 30 seconds, but target culturants could delay the loss of those consequences. The analog of negative reinforcement, as well as that of positive reinforcement, selected target culturants without the interference of accidental punitive contingencies.